Centros de internação: o trabalho em meio a estigmas, agressões e afetos - saúde mental dos agentes e segurança socioeducativos - Saulo Rodrigues de Moraes (2008)
The objective of this research was to identify factors that causing distress to the staff security workers, responsible for security inside and outside the walls of the detention centers for teenagers in conflict with the law. Rescued the history of this professional category in Minas Gerais and investigates aspects of work in detention center in the metropolitan area of Belo Horizonte, that impact their mental health, and the strategies used by them to prevent illness. Two cases studies it was used in this research, ergonomic observations, questionnaries and research and documentary sources. The study showed that this category is struggling by inherents to the nature of the work, marked by the paradoxical requirements, such as trust, distrust; be tough and tender, educate watching and watching educating. The conclusion was that this characteristics associated with another types of stress, among them, those that cause the Burnout Syndrome, are responsible for the suffering of the worker staff. The two cases studied also showed that some agents develops strategies to preserver and increase their health in the midle of stigmate, agression and affection.